Myth and Madness in Grupo Galpão's Expressionistic Production of Álbum de família - Alves, Junia C. M.; Noe, Marcia (Latin American Theatre Review, 2002)
A number of scholars have discussed the mythic elements in Nelson Rodrigues’s Álbum de Família, an emphasis present in Grupo Galpão’s award-winning production that was staged in Belo Horizonte in 1990. This essay discusses the expressionistic techniques that were used to articulate the play’s mythic dimensions, particularly its use of Mircea Eliade’s notion of the eternal return, a cyclical concept of human existence. Similarly, the theme of madness as a higher form of consciousness pervades the play, emphasized through expressionistic staging. Because form is so adroitly married to theme in this innovative production, it is entirely worthy of the critical accolades and prizes it received. (JCMA/MN)